PENGARUH STRATEGI PEMBELAJARAN HIJAU KUNING MERAH TERHADAP HASIL BELAJAR PPKn SISWA KELAS XI SMA N 9 PEKANBARU - Febriani, Nurwulan; Erlinda, Sri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: Learning strategies are plans that countain a series of activities designed to achieve certaineducational goals. This research aims as follow know the effect of using green yellow red learning strategies on student learning outcomes in class XI SMA N 9 Pekanbaru. The subject of this study was the students of class XI SMA N 9 Pekanbaru which consisted of 9 classes wit a total number of students of 318 people. The sample in this study was to use homogeneity test taken 2 class randomly class XI IPA 1 as a control class and class XI IPA 5 as an experimental class. Data is collected through observation, tests and documentation. The design used is the pre-test and post-test in the quasi-experimental design. The results showed that based on the analysis of data acquisition that has been done using the statistical t test obtained price tarithmetic > ttable this proves that green yellow red learning strategies have a significant effect on improving student learningoutcomes with the average acquisition of student learning outcomes is 93.19 %. Based on the analysis of the different t test there are two classed showing tarithmetic > ttable (70.4> 1,99444), added with the contribution of the gain obtained from the experimental class of 0,712 which means it is effective to use. Thus the use of green yellow red learning strategies has a positive and significant impact on student learning outcomes in PPKn subjects in class XI SMA N 9 Pekanbaru.Key Words: Green yellow res learning strategies, learning outcome